Palm oil mill effluent for lipid production by the diatom thalassiosira pseudonana - Karthick Murugan, Palanisamy; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim; Natanamurugaraj, Govindan (MDPI, 2022)
Biomass and lipid production by the marine centric diatom Thalassiosira pseudonana were characterized in media based on palm oil mill effluent (POME) as a source of key nutrients. The optimal medium comprised 20% by volume POME, 80 µM Na2SiO3, and 35 g NaCl L−1 in water at pH ~7.7. In 15-day batch cultures (16:8 h/h light–dark cycle; 200 µmol photons m−2 s−1, 26 ± 1◦C) bubbled continuously with air mixed with CO2 (2.5% by vol), the peak concentration of dry biomass was 869 ± 14 mg L−1 corresponding to a productivity of ~58 mg L−1 day−1 . The neutral lipid content of the biomass was 46.2 ± 1.1% by dry weight. The main components of the esterified lipids were palmitoleic acid methyl ester (31.6% w/w) and myristic acid methyl ester (16.8% w/w). The final biomass concentration and the lipid content were affected by the light–dark cycle. Continuous (24 h light) illumination at the above-specified irradiance reduced biomass productivity to ~54 mg L−1 day−1 and lipid content to 38.1%.